The anti-migratory effects of FKBPL and its peptide derivative, AD-01: regulation of CD44 and the cytoskeletal pathway. - Anita Yakkundi; Lynn McCallum; Anthony O'Kane; Hayder Dyer; Jenny Worthington; Hayley D McKeen; Lana McClements; Christopher Elliott; Helen O McCarthy; David G Hirst; Tracy Robson (PLoS ONE)
FK506 binding protein-like (FKBPL) and its peptide derivatives exert potent anti-angiogenic activity in vitro and in vivo and control tumour growth in xenograft models, when administered exogenously. However, the role of endogenous FKBPL in angiogenesis is not well characterised. Here we investigated the molecular effects of the endogenous protein and its peptide derivative, AD-01, leading to their anti-migratory activity. Inhibition of secreted FKBPL using a blocking antibody or siRNA-mediated knockdown of FKBPL accelerated the migration of human microvascular endothelial cells (HMEC-1). Furthermore, MDA-MB-231 tumour cells stably overexpressing FKBPL inhibited tumour vascular development in vivo suggesting that FKBPL secreted from tumour cells could inhibit angiogenesis. Whilst FKBPL and AD-01 target CD44, the nature of this interaction is not known and here we have further interrogated this aspect. We have demonstrated that FKBPL and AD-01 bind to the CD44 receptor and inhibit tumour cell migration in a CD44 dependant manner; CD44 knockdown abrogated AD-01 binding as well as its anti-migratory activity. Interestingly, FKBPL overexpression and knockdown or treatment with AD-01, regulated CD44 expression, suggesting a co-regulatory pathway for these two proteins. Downstream of CD44, alterations in the actin cytoskeleton, indicated by intense cortical actin staining and a lack of cell spreading and communication were observed following treatment with AD-01, explaining the anti-migratory phenotype. Concomitantly, AD-01 inhibited Rac-1 activity, up-regulated RhoA and the actin binding proteins, profilin and vinculin. Thus the anti-angiogenic protein, FKBPL, and AD-01, offer a promising and alternative approach for targeting both CD44 positive tumours and vasculature networks.